COMPREHENSIVE RESEARCH REPORT AND ANNOTATED TRANSLATION: APPLICATION OF INSPIRATORY MUSCLE TRAINING ON DYSPNEA SCALE AND IMPACT OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) - Indra Frana Jaya; M. Agung Akbar (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a debilitating lung condition characterized by persistent respiratory difficulties, with dyspnea (shortness of breath) acting as the primary symptom that severely compromises patients' quality of life. Inspiratory Muscle Training (IMT) represents a targeted intervention designed to enhance the strength of respiratory muscles and alleviate dyspnea symptoms in individuals suffering from COPD. Purpose: The primary objective of this study is to analyze the effect of IMT on the impact of COPD and the dyspnea scale. Methods: The research employed a quasi-experimental design utilizing two distinct groups: an intervention group and a control group. The study population consisted of 80 COPD patients admitted to the internal medicine ward of a general hospital. Data collection utilized the COPD Assessment Test (CAT) and the Modified Medical Research Council (mMRC) dyspnea scale to quantify the impact of COPD and the severity of breathlessness. Patients in the intervention group received IMT sessions twice a day for one day, administered consecutively for three days, with each session lasting approximately 10–20 minutes. Results: The Friedman test was utilized to evaluate the statistical significance of differences in COPD impact and dyspnea scales across three specific measurement points: baseline (initial), day 2, and day 3. The findings demonstrated a significant reduction in both the impact of COPD and the dyspnea scale within the intervention group (p = 0.001). Conversely, the control group exhibited changes only in the dyspnea scale (p = 0.037), with no significant improvement in the overall impact of COPD. Conclusion: The study concludes that IMT is proven effective in increasing respiratory muscle strength, improving pulmonary ventilation, and reducing symptoms of shortness of breath in COPD patients. Furthermore, the role of nurses in the implementation of IMT is identified as critical for maximizing the therapeutic benefits, thereby reducing the impact of COPD and dyspnea.   Keywords: COPD, Dyspnea, Impact of COPD, Inspiratory Muscle Training, Nursing Intervention.